Re-assessment of the threat status of three Red Data List plant species: brachystelma gerrardii, senecio triodontiphyllus and streptocarpus fasciatus - Makgopo, Katlego (My University, 2022)
Plants provide fundamental support systems and resources for life on earth, they serve as the foundation of ecosystems. However, many plant species are rapidly going extinct and will soon disappear. The threat assessments of plants are important as they inform which species are most at risk and call for immediate management attention and conservation. The first step to initiate conservation actions for endangered organisms is identifying species that are in decline or face extinction. A previous study for the management of Pullen Nature Reserve found that there are threatened plant species that occur on the property and in the conservancy. These plants are: (1) Brachystelma gerrardii Harv., (2) Senecio triodontiphyllus C. Jeffrey, and Streptocarpus fasciatus T. J Edwards & Kunhardt. Brachystelma gerrardii has a distribution from KwaZulu-Natal to the Waterberg in Limpopo, and is currently classified as Endangered (EN) according to the IUCN Categories and Criteria,. Senecio triodontiphyllus has a distribution that is restricted to the Mpumalanga province, from Barberton to Kaapmuiden. This species is currently classified as Vulnerable (VU). Streptocarpus fasciatus is endemic to South Africa and occurs in Mpumalanga. Its distribution ranges from Nelspruit to Kaapmuiden. This species has a current threat status of VU. Brachystelma gerrardii, S. triodontiphyllus and S. fasciatus were chosen for this study because they are rare, endangered and have restricted distributional ranges. A re-assessment of their threat status is important as the previous assessments are out of date. Thus, the aim of this project is to re-assess the threat status of three plant species B. gerrardii, S. fasciatus and S. triodontiphyllus; to assess the potential effect of climate change on current and future distributions of these plant species; as well as to investigate aspects of the reproductive ecology of S. fasciatus. The IUCN Red List Categories and Criteria were used to perform the assessments; these criteria are objective, quantifiable and have been used over many years. This project was carried out in three stages, (1) an analysis of herbarium specimens as well as fieldwork to collect data on species habitats, range sizes, population sizes, as well as Area of occupancy (AOO) and Extent of occurrence (EOO) among other information to determine the current threat status of the species; (2) an analysis of current and future climate data to determine the impact of climate change on plant species distributions; and lastly, (3) investigating the breeding strategy used by S. fasciatus, to determine whether pollination and germination have implications for the threat status. Results from herbarium records and fieldwork revealed eleven, five and six sub-populations for B. gerrardi, S. fasciatus and S. triodontiphyllus respectively. According to the MaxEnt models for B. gerrardii and S. triodontiphyllus, areas that are currently suitable for the growth of these plants are predicted in the eastern parts of South Africa from East London through KwaZuluNatal and Mpumalanga, towards the northern parts of Limpopo. Current suitable areas for S. fasciatus are predicted as patches along the coast in Western cape, along the border of Lesotho in KwaZulu-Natal, in parts of Gauteng as well as the eastern parts of Mpumalanga. Future iv predictions for 2050 using the A1B and A2 emission scenarios showed a decrease in suitable habitats for B. gerrardi and S. triodontiphyllus, but a significant increase in the suitable habitat for S. fasciatus. Field studies on the pollination of S. fasciatus show that this plant may be pollinated by a nemestrinid fly belonging to the genus Stenobasipteron, and the results also indicate the presence of a mixed breeding system involving self-pollination and cross-pollination. A low seed set was observed in open pollinated flowers, indicating that the species may be pollinator limited, however, this observation may also be as a result of the species’ very specific habitat requirements. This may contribute to its low population size and thus its threatened status. According to the results of the IUCN threat assessment, S. fasciatus was found to be vulnerable (VU) under Criterion D (subcriteria D1 and D2), and S. triodontiphyllus was found to be endangered (EN) under subcriteria D1. Brachystelma gerrardii remains classified as EN as per the threat assessment by Styles and von Staden in 2007. Based on the results of this study further investigations are required with regards to the breeding system of S. fasciatus, and all three of these plant species are in need of immediate conservation actions.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Brachystelma gerrardii; Senecio triodontiphyllus; Streptocarpus fasciatus